2000
DOI: 10.1073/pnas.230285997
|View full text |Cite
|
Sign up to set email alerts
|

Mice with a targeted mutation in the thyroid hormone β receptor gene exhibit impaired growth and resistance to thyroid hormone

Abstract: Patients with mutations in the thyroid hormone receptor ␤ (TR␤) gene manifest resistance to thyroid hormone (RTH), resulting in a constellation of variable phenotypic abnormalities. To understand the molecular basis underlying the action of mutant TR␤ in vivo, we generated mice with a targeted mutation in the TR␤ gene (TR␤PV; PV, mutant thyroid hormone receptor kindred PV) by using homologous recombination and the Cre͞loxP system. Mice expressing a single PV allele showed the typical abnormalities of thyroid f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
261
1
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 250 publications
(282 citation statements)
references
References 34 publications
19
261
1
1
Order By: Relevance
“…As TSH is a major regulator of thyrocyte proliferation (Rivas and Santisteban, 2003), we first compared thyroid hormone and TSH levels in TRb PV/PV PPARg þ / þ and TRb PV/PV PPARg þ /À mice. Consistent with previous findings (Kaneshige et al, 2000;Kato et al, 2004), total serum L-thyroxine (TT4) (Figure 4a PPARg insufficiency activates the NF-kB signaling pathway in thyroid tumors Using cDNA microarrays, we previously identified the NF-kB signaling as one of the altered pathways associated with thyroid carcinogenesis of TRb PV/PV PPARg þ / þ mice (Ying et al, 2003a). It has recently been shown that PPARg insufficiency causes activation of the NF-kB pathway in B cells of PPARg þ /À mice (Setoguchi et al, 2001).…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…As TSH is a major regulator of thyrocyte proliferation (Rivas and Santisteban, 2003), we first compared thyroid hormone and TSH levels in TRb PV/PV PPARg þ / þ and TRb PV/PV PPARg þ /À mice. Consistent with previous findings (Kaneshige et al, 2000;Kato et al, 2004), total serum L-thyroxine (TT4) (Figure 4a PPARg insufficiency activates the NF-kB signaling pathway in thyroid tumors Using cDNA microarrays, we previously identified the NF-kB signaling as one of the altered pathways associated with thyroid carcinogenesis of TRb PV/PV PPARg þ / þ mice (Ying et al, 2003a). It has recently been shown that PPARg insufficiency causes activation of the NF-kB pathway in B cells of PPARg þ /À mice (Setoguchi et al, 2001).…”
Section: Resultssupporting
confidence: 93%
“…The mice harboring the TRbPV gene were prepared and genotyped as described previously (Kaneshige et al, 2000). Two-month-old male TRb PV/PV mice were fed an AIN-76A diet (Bio Serve, Frenchtown, NJ, USA) mixed with (n ¼ 14) or without (n ¼ 13) rosiglitazone (20-80 mg/kg/day; Avandia, GlaxoSmithKline, Research Triangle Park, NC, USA) for 7-8 months.…”
Section: Experimental Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…The different phenotypes could reflect the differences in their differential T3 binding ability, diverse potency of dominant negative effect, and variable interaction of nuclear receptor coregulators Tinnikov et al, 2002;Liu et al, 2003). Unlike the abnormalities in WAT found in TRα1 knock-in mice, no apparent change in mass or morphology of WAT was observed in TRβPV mice, in which PV was targeted to the TRβ gene locus (Kaneshige et al, 2000;Araki et al, 2009), indicating that TRα1 plays a critical role in the regulation of lipid homeostasis in WAT.…”
Section: Regulation Of Lipid Homeostasis and Adipogenesis In White Admentioning
confidence: 99%
“…We have created a mutant mouse by targeting a mutation (PV) to the TR␤ gene locus (TR␤PV mice) (3). PV was identified in a patient (PV) with resistance to thyroid hormone (RTH) (4).…”
mentioning
confidence: 99%